2020
DOI: 10.1111/ctr.14075
|View full text |Cite
|
Sign up to set email alerts
|

Uniqueness of laryngeal nerve injury following heart transplantation

Abstract: Background: The incidence of recurrent laryngeal nerve injury (RLNI) after heart transplantation has not been well studied. This can manifest as vocal cord dysfunction causing dysphonia. Previous research is limited to aortic, coronary bypass, and valvular surgery. Identifying RLNI after heart transplantation is important in order to more accurately detail complications associated with this major surgery. Methods: This is a retrospective study assessing 972 adult patients who underwent orthotopic heart transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
2
2
Order By: Relevance
“…12,19,34 Angelo et al found that the incidence of newly established recurrent laryngeal nerve injuries in HTPL patients was 2.9%, which was higher than that in general cardiothoracic surgery but lower than that in aortic arch surgery. [35][36][37] Our data show that the incidence of vocal cord abnormalities was higher than in previous reports. It could be because we enrolled all patients with impaired vocal fold motion (vocal cord paresis), and some of them showed improvement over time.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…12,19,34 Angelo et al found that the incidence of newly established recurrent laryngeal nerve injuries in HTPL patients was 2.9%, which was higher than that in general cardiothoracic surgery but lower than that in aortic arch surgery. [35][36][37] Our data show that the incidence of vocal cord abnormalities was higher than in previous reports. It could be because we enrolled all patients with impaired vocal fold motion (vocal cord paresis), and some of them showed improvement over time.…”
Section: Discussioncontrasting
confidence: 65%
“…Angelo et al. found that the incidence of newly established recurrent laryngeal nerve injuries in HTPL patients was 2.9%, which was higher than that in general cardiothoracic surgery but lower than that in aortic arch surgery 35–37 . Our data show that the incidence of vocal cord abnormalities was higher than in previous reports.…”
Section: Discussioncontrasting
confidence: 55%
“…According to the International Society for Heart and Lung Transplantation registry, the number of global heart transplants is nearing 6000 every year. 33 Compared to the number of HF patients, heart transplantation is difficult to popularize obviously. Other complications such as allograft rejection also limits its application.…”
Section: Heart Transplantationmentioning
confidence: 99%
“…Heart transplantation is a more viable option for appropriate patients with end‐stage cardiac disease with the improvement of immunosuppression and surgical techniques. According to the International Society for Heart and Lung Transplantation registry, the number of global heart transplants is nearing 6000 every year 33 . Compared to the number of HF patients, heart transplantation is difficult to popularize obviously.…”
Section: Hf Classification and Conventional Treatmentsmentioning
confidence: 99%